PENGARUH EARNING POWER DAN FIRM SIZE TERHADAP EARNING MANAGEMENT PADA PT. ELNUSA, TBK PERIODE 2008-2017 - Sakinah, Gina; Murtadho, Taufiq Ridwan (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2021)
Financial statements become the main source of information for all parties because it provides an overview of the state of the company's performance for a certain period. Company profit information will provide an overview of the company's ability to manage the company effectively and efficiently. Earning management is an action taken by the manager in the presentation of financial statements. Earning power the company's ability to generate profit in each period. Firm size is a scale that classifies the size of a company by assessing the total level of assets, stock market value, log size, and others. This research uses descriptive methods and quantitative approaches using secondary data supported by literature and documentation studies. The results showed partial earning power has a significant influence on earnings management. But firm size has no significant effect on earnings management. Simultaneously, both free variables can contribute and can significantly affect earnings management with a contribution of 58.5%. Â  Keywords: Earning Power, Firm Size, Earnings Management